Educational service quality and student satisfaction at public higher educational institutions in Malaysia : an expectation-perception importance analysis / Abdul Raheem Mohamad Yusof - Mohamad Yusof, Abdul Raheem (2008)
This dissertation examines Educational Service Quality and Student Satisfaction at Public Higher Educational Institutions (PHEI5) in Malaysia. In the quest to be a centre of academic excellence, the government of Malaysia is very concern about the quality of higher educational institutions in Malaysia. This study attempts to investigate: the determinants of educational service quality and the importance of the various dimensions of quality; the differences between expected service and perceived service;the level of customer satisfaction; the relationship between educational service quality and customer satisfaction; the implications of the moderating variables; and the Educational Service Quality and Student Satisfaction Index (ESQSSi) for the Malaysian PHEIs. A research framework was developed and thirteen hypotheses were formulated.The study employed a self-administered questionnaire based on a synthesized instrument and was cross-sectional in nature. A total of 517 post-graduate students from four PHEIs participated in this study. Data was collected using a 166-item structured questionnaire and a simple random sampling was employed. ANOVA, regression analysis, the American Customer Satisfaction Index (ACSI) calculation method, and the differencing technique were used to analyze the data.